2021
DOI: 10.1007/s10578-021-01252-0
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Account on Parents’ Use of and Attitudes Towards Time-Out

Abstract: Time-out (TO) is a well-established technique for effectively managing childhood conduct problems, yet there is increasing controversy around its use. Using a mixed-methods approach, we investigated the impact of recent criticisms against TO on parents’ use of and attitudes towards it. A community sample of parents ( N = 297, M age = 37.14) completed an online survey (Study 1) to investigate use of and acceptability of TO. Results showed that 57.91% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…With regard to BPT, the use of timeout—i.e., a core component of BPT, whereby a child is placed in a safe, neutral space for a brief period of time away from parent attention (Kaminski et al, 2008 )—has been the source of ongoing debate among practitioners and researchers, with many parents and professionals re-evaluating its strengths and challenges [see Dadds and Tully ( 2019 ) for a recent review]. Moreover, a recent community-based study exploring why some parents prefer not to use timeout found that they favor alternative parenting strategies believed to value connection, “attachment,” and co-regulation in the parent–child relationship (Canning et al, 2021 ). In summary, although BPT has a substantial evidence base and is widely disseminated, there is a timely need to investigate the collective evidence for alternative models of parenting interventions targeting EXT and INT that may be better suited to parents who prefer and value relational and emotion-oriented approaches to parenting.…”
Section: Behavioral Parenting Interventionsmentioning
confidence: 99%
“…With regard to BPT, the use of timeout—i.e., a core component of BPT, whereby a child is placed in a safe, neutral space for a brief period of time away from parent attention (Kaminski et al, 2008 )—has been the source of ongoing debate among practitioners and researchers, with many parents and professionals re-evaluating its strengths and challenges [see Dadds and Tully ( 2019 ) for a recent review]. Moreover, a recent community-based study exploring why some parents prefer not to use timeout found that they favor alternative parenting strategies believed to value connection, “attachment,” and co-regulation in the parent–child relationship (Canning et al, 2021 ). In summary, although BPT has a substantial evidence base and is widely disseminated, there is a timely need to investigate the collective evidence for alternative models of parenting interventions targeting EXT and INT that may be better suited to parents who prefer and value relational and emotion-oriented approaches to parenting.…”
Section: Behavioral Parenting Interventionsmentioning
confidence: 99%
“…Media messaging and public and professional dialogue conspicuously feature two inter-related concerns about time-out, namely, that it (1) causes harm in otherwise healthy children, and that it (2) exacerbates existing difficulties in children who have experienced trauma, despite evidence to the contrary on both counts [ 12 ]. Parents are beginning to echo and amplify high-profile media criticisms of time-out, contributing to perception that it is ineffective and harmful [ 18 ]. In the clinical context, understanding and addressing parental concerns is essential, as—in terms of parent engagement—the empirical evidence relating to whether time-out causes harm is perhaps less relevant than a parent’s concern that it might .…”
Section: Broader Influences/environmentmentioning
confidence: 99%
“…Yet despite this empirical evidence of time-out’s safety when used appropriately, the strategy remains one of the more divisive and technically challenging parenting techniques. In recent years there has been growing public concern around the safety and appropriateness of time-out [ 12 , 18 ], fuelled by articles in popular press publications and online material; these claims have been described as “wild and unsubstantiated, yet highly visible” [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure has proved to be one of the most popular forms of discipline with parents, both in the United States and other countries [ 1 , 2 , 21 ]. For example, in Australia, it is used by between 58% and 80% of parents [ 19 , 22 ]. Both the American Academy of Pediatrics and the American Academy of Child and Adolescent Psychiatry recommend time-out as an effective parenting strategy.…”
Section: Introductionmentioning
confidence: 99%